System design analysis for replacement of coal power plants with small nuclear reactors - Pope, Jason, author; Bradley, Thomas H., advisor; Coburn, Timothy, advisor; Young, Peter, committee member; Ellison, Nicole, committee member (Colorado State University. Libraries, 2025)
Coal power plants are the predominant energy generation technology in many countries and are a major global source of greenhouse gas emissions. A variety of policy and economic pressures are driving the replacement of this legacy technology, but the electricity generated by retiring coal power plants must be replaced and the generation capacity must be increased to meet projected electricity demand growth. A diversity of alternatives to coal generation, including nuclear power, are key components of nearly-every study of a future sustainable electricity sector. At present, small nuclear reactors have been proposed and planned by researchers, utilities, and governments to enable on-site replacement of existing coal power generators. By directly replacing coal power plants with nuclear reactors, these programs seek to develop zero-emissions, high-reliability electricity generation, at lower cost than would be possible in green-field developments. In order to assess the role that proposed coal-to-nuclear conversions could play in adoption of small nuclear generators, a variety of problems would need to be addressed. First, an improved understanding of the value of existing infrastructure at coal power plant sites is needed to assess the economic value of coal-to-nuclear conversion. Second, the schedule efficiencies available from the coal-to-nuclear conversion concept is, to date, unknown. The extent to which regional emissions trajectories would be accelerated or delayed by coal-to-nuclear conversion is unknown. Existing research has investigated the possibility of reusing operating infrastructure at coal power plants, including buildings and improvements, turbine plant equipment, electric plant equipment, and condenser and heat rejection systems. These studies hypothesize that costs, schedule, and overall emissions at reconstituted generation sites would be improved. However, detailed costing, scheduling and electricity sector transformation modeling evidence has not been generated, particularly at both the local and the global scale. To address these research gaps, this investigation specifically pursues two streams of research: (1) assessing the economic value and schedule efficiencies associated with retaining the available grid connection and cooling water at potential coal-to-nuclear sites across the United States (U.S.), and (2) assessing the global decarbonization potential associated with coal-to-nuclear conversion, with a key emphasis on modeling this transition within the U.S. and India, as these are the countries having the world's largest coal-fired power generation capacity outside of China. Results from the first area of research indicate that, when installing a single 300 MW nuclear reactor, the use of the existing cooling water source and method can save $6.8M - $23.5M annually depending on the cooling method chosen at the new site, with expected savings of $13.3M. Expected savings across the fleet are valued at $1.7B - $4.5B annually, depending on the number of reactors installed. The value of existing electrical grid connections for the 300 MW reactor can range from $25M to $53.6M, depending on geographic location, with existing grid connections across the fleet valued from $5.3B – $10.1B, again depending on the number of reactors installed. In the second area of research, schedule and timelines for coal-to-nuclear conversion are assessed, and the resulting emissions reductions are determined to help better understand the impact that a fleet-scale nuclear conversion campaign could have on decarbonization goals in both the U.S. and India. Results indicate that, while the U.S. and India presently have similar installed coal generation capacity and annual emissions, India's remaining committed emissions are approximately five times greater than those of the U.S. for both a base case and a very high-rate (46-plants across the U.S. by 2038) conversion case. Converting coal power plants to nuclear plants do realize reductions in committed GHG emissions, but the degree of national impact relies heavily on fleet composition. Nations with older generation fleets (such as the U.S.) realize annual emissions reductions from both retirements and conversions, but their committed emissions reductions are dominated by reductions due to retirements. For nations with younger fleets, coal-to-nuclear conversions have a much greater impact on committed emissions, indicating the potential of coal-to-nuclear conversion to realize global emission reductions, because the global coal fleet is relatively young (compared to the U.S. coal fleet). Collectively, these findings suggest that while U.S. decarbonization potential resulting from coal-to-nuclear conversions is limited, existing electrical grid connections and cooling water availability at existing coal power sites represent economic value that should be considered, along with other factors, by entities considering siting alternatives for small nuclear reactor installation. Both potential emissions reductions and the economic value of repowering the site, along with other factors, should be considered in the coal-to-nuclear adoption decision.
Keywords: cooling; generation; nuclear; energy; coal; grid